2011
DOI: 10.1021/nn103286r
|View full text |Cite
|
Sign up to set email alerts
|

Exchange Coupling Interaction in L10-FePd/α-Fe Nanocomposite Magnets with Large Maximum Energy Products

Abstract: Nanocomposite magnets (NCMs) consisting of hard and soft magnetic phases are expected to be instrumental in overcoming the current theoretical limit of magnet performance. In this study, structural analyses were performed on L1(0)-FePd/α-Fe NCMs with various hard/soft volume fractions, which were formed by annealing Pd/γ-Fe(2)O(3) heterostructured nanoparticles and pure Pd nanoparticles. The sample with a hard/soft volume ratio of 82/18 formed by annealing at 773 K had the largest maximum energy product (BH(ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
50
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(52 citation statements)
references
References 39 publications
1
50
0
1
Order By: Relevance
“…The recent patents filed in this topic can be divided in three different categories: (i) the ones based on rare-earth hard magnets (FeNdB or SmCo) coupled to high moment soft magnets such as Fe or FeCo [ [47][48][49][50][51][52][53][54][55][56][57][58] (ii) nanoparticles of hard magnets based on precious metals (e.g., FePt or FePd) coupled to Fe, Fe 3 Pt, Fe 3 O 4 or FeCo [54,55,[59][60][61][62][63]and (iii) novel structures based on rare-earth and precious-metals free hard magnets (-Fe 2 O 3 , MnAl, MnBi, Ba-ferrite or Co 3 C), coupled to soft materials (e.g., Fe, FeCo, FeNi or Co 2 C) [53][54][55][65][66][67][68][69][70][71]. Although most of the proposed systems are based on conventional structures, i.e., where the hard magnet is in the core, some notable exceptions are Fe/-Fe 2 O 3 and Co/Co 3 C which, since the hard magnet is obtained by the surface treatment of the core, they have an inverse soft/hard structure [66,71].…”
Section: Permanent Magnetsmentioning
confidence: 99%
“…The recent patents filed in this topic can be divided in three different categories: (i) the ones based on rare-earth hard magnets (FeNdB or SmCo) coupled to high moment soft magnets such as Fe or FeCo [ [47][48][49][50][51][52][53][54][55][56][57][58] (ii) nanoparticles of hard magnets based on precious metals (e.g., FePt or FePd) coupled to Fe, Fe 3 Pt, Fe 3 O 4 or FeCo [54,55,[59][60][61][62][63]and (iii) novel structures based on rare-earth and precious-metals free hard magnets (-Fe 2 O 3 , MnAl, MnBi, Ba-ferrite or Co 3 C), coupled to soft materials (e.g., Fe, FeCo, FeNi or Co 2 C) [53][54][55][65][66][67][68][69][70][71]. Although most of the proposed systems are based on conventional structures, i.e., where the hard magnet is in the core, some notable exceptions are Fe/-Fe 2 O 3 and Co/Co 3 C which, since the hard magnet is obtained by the surface treatment of the core, they have an inverse soft/hard structure [66,71].…”
Section: Permanent Magnetsmentioning
confidence: 99%
“…[15][16] Magnetic energy product ((BH) max ) of 8.1 MGOe with H c = 3.0 kOe was obtained for L1 0 -FePd nanoparticles with size in the range of 30-50 nm. 17 When 18 % Fe was introduced, (BH) max was enhanced to 10.3 MGOe with slight reduced H c (2.1 kOe) due to strong exchange coupling effect between magnetic hard L1 0 -FePd and soft α-Fe grains. 17 Nevertheless, high cost of MgO(001) single crystal substrate and the inaccessible control on size distribution and compacted assembly make them not 3 favorable for practical applications.…”
Section: Introductionmentioning
confidence: 94%
“…17 When 18 % Fe was introduced, (BH) max was enhanced to 10.3 MGOe with slight reduced H c (2.1 kOe) due to strong exchange coupling effect between magnetic hard L1 0 -FePd and soft α-Fe grains. 17 Nevertheless, high cost of MgO(001) single crystal substrate and the inaccessible control on size distribution and compacted assembly make them not 3 favorable for practical applications. For polycryatalline FePd films grown on non-textured substrates like glass or SiO 2 /Si typically show weak hard magnetism no matter applied with in-situ or post heat treatment.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…To date, limited attempts have been made to prepare fct-FePd/Fe nanocomposites. [24,[27][28][29] Yu et al reported the synthesis of fct-FePd/Fe nanocomposites annealed from urchin-like FePd-Fe 3 O 4 composites. [27] By promoting the interfacial diffusion between Pd and Fe, fct-FePd/Fe nanocomposites could also be obtained from the mixture of Pd/Fe 2 O 3 and Pd NPs, in which extra Pd NPs were used to control the volume fraction of hard/soft magnetic phases in the nanocomposites.…”
Section: Introductionmentioning
confidence: 99%